Effectual forms of chicken eggshell to improve soil pH and exchangeable bases (K, Ca and Mg) of peat soil / Muhammad Nazif Hussin - Hussin, Muhammad Nazif (Faculty of Plantation and Agrotechnology, 2019)
Low soil pH is one of the synonym characteristics of peat soils which restricted the nutrient availability in the soils. Even though the liming application using either agriculture lime, burned lime or hydrated lime is quite common in Malaysia, there is a potential of chicken eggshell to become a substitution for these types of lime, especially in a small scale agricultural area. This study intends to determine the exchangeable bases concentration of chicken eggshell in powder, liquid and crumb forms as well as to evaluate the effects on soil pH. The results were compared to the calcium carbonate (CaCOɜ) lime to evaluate the effectiveness of the chicken eggshells. From this study, the findings showed that the chicken eggshell in powdered form has significant effects in improving peat soil pH and calcium (Ca) concentration compared to other treatments. It is suggested that the chicken eggshell in powdered forms may have a potential as a substitution of lime with lower cost.